The Influence of Various Role Models on Children’s Pro-environmental Behaviours - Liang, Mingyue; Chen, Qianying; Zhou, Yanyan (Frontiers in Psychology, 2022)
Although most schoolchildren can dispose of their own litter, they are typically not sensitive to environmental issues in the school’s public areas. How do we improve children’s sensitivity to public environments and cultivate pro-environmental behaviours? Based on Bandura’s social learning theory, this study explored the effects of various role models (teachers and peers) on the pro-environmental behaviours of children aged 7–13. A field study was conducted in which examples of postprandial garbage disposal behaviours were provided using role models and the subsequent behaviours of the children were observed. We located the experiment in a real educational context and manipulated the type of role model (teacher or peer) and the behaviour being modelled (positive behaviours involving picking up litter or negative behaviours involving littering). The results showed that different role models had different effects on the subjects’ pro-environmental behaviours. Only positive demonstration by teachers significantly improved the subjects’ pro-environmental behaviours, that is, teachers’ picking up of garbage in front of children significantly improved the children’s attention to the environment and their adoption of pro-environmental behaviours. Positive demonstration by peers, negative demonstration by teachers and negative demonstration by peers had no impact on the children’s pro-environmental behaviours. The results demonstrate that teachers must be mindful of their role as role models in the educational environment and facilitate students’ development of pro-environmental behaviours.